Efficacy and safety of once daily fluticasone furoate nasal spray for treatment of irritant (non-allergic) rhinitis - Pongsakorn Tantilipikorn (2018)
© Tantilipikorn et al. Introduction: The safety and efficacy of fluticasone furoate nasal spray (FFNS) for the symptoms of seasonal and perennial allergic rhinitis have been previously demonstrated in several clinical studies. The objective of this pilot study was to compare the efficacy and safety of FFNS 110 mcg once daily with placebo in patients with irritant (nonallergic) rhinitis triggered predominantly by air pollution. Methods: This was a randomized, double-blind, placebo-controlled, 4-week study of subjects in Thailand with irritant rhinitis who received either FFNS 110 mcg (N=53) or placebo (N=49) once-daily. Subjects with a ≥2 year history of air pollution as their predominant rhinitis trigger, negative skin test to local seasonal/perennial allergens, positive histamine skin test, and normal sinus radiograph were enrolled if they met minimum reflective total nasal symptom score (rTNSS) ≥4.5 (maximum=9) and a nasal congestion score of ≥2 (maximum =3). All were assessed for nasal eosinophilia at study entry and completion. Air quality was monitored throughout the study. The primary efficacy endpoint was the mean change from baseline over the treatment period in daily rTNSS, the average of the morning and evening rTNSS. The key secondary measure was the mean change from baseline over the entire treatment period in morning pre-dose instantaneous total nasal symptom score (iTNSS). Results: The Air Quality Index (AQI) during the study generally did not reach unhealthy levels. Baseline daily rTNSS scores were similar between treatment groups (FFNS=6.7; placebo=6.4). The least square mean change from baseline in rTNSS was -2.17 and -2.10 for FFNS and placebo, respectively, with a difference of -0.065 (p=0.845). Gradual improvements were seen in both treatment groups for iTNSS; however, the treatment difference (-0.075) was not statistically significant (p=0.827). Additionally, there were no statistically significant differences between treatment groups for AM and PM rTNSS, individual nasal symptoms, daily reflective, AM and PM reflective and AM pre-dose instantaneous total ocular symptom scores (TOSS) or individual ocular symptom scores. Nasal cytology at baseline found more than two-thirds of subjects had <20% eosinophils. Adverse events were few and similar between groups and noted as mild in intensity. Conclusion: Subjects receiving FFNS had similar improvement to placebo in their rhinitis symptoms. The lack of a treatment effect may be in part due to the overall good air quality present throughout the study or an insufficient dose or duration of FFNS. The safety findings showed FFNS 110 mcg once daily to be well tolerated.